Desain dan Pemasangan Pergola Rambatan Tanaman Menjalar sebagai Ikon Perumahan - Syamsul Hadi; Bambang Irawan; Purwoko Purwoko; Haris Puspito Buwono; Anggit Murdani (LPPM UNINUS, 2021)
The problems faced are the lack of beauty and obstructed views at the mouth of the road where there is a narrow brick gate access and the difficulty of installing decorations during the commemoration of the Independence Day of the Republic of Indonesia. The purpose of community service is to improve the beauty of the environment and ease when installing decorations of August and wider entry-exit access points. The method applied is consultation with residents to determine the design of the pergola from rectangular pipe construction that can be propagated by vascular plant such as grapes/passion fruit/betel, making pergola, and demolishing gates, installing a construction frame with cast-concrete foundation legs so that they are sturdy and not corroded, assessing the robustness and beauty of the placement, and submitting it to the Head of the neighborhood Association. The results obtained are in the form of wider access roads for 2 sedans passing each other, the driver's view is not blocked, the beauty is increased, and the installation of the decoration can be easier. The installation of a pergola can have the implication of making traffic flow smoother and residents must be more careful, especially children who cross the road in front of their houses with the conclusion that pergola vascular plant can be used as a housing icon, resulting in a synergy between the State Polytechnic Malang and residents who are satisfied with the assistance and beauty of the environment in the RT 03-RW 06 Tasikmadu, Lowokwaru, Malang city.